Progression of incomplete toward complete left bundle branch block: A clinical and electrocardiographic analysis. Issue 4 (11th December 2019) - Senesael, Ellie; Calle, Simon; Kamoen, Victor; Stroobandt, Roland; De Buyzere, Marc; Timmermans, Frank; De Pooter, Jan
Abstract: Background: Complete left bundle branch block (cLBBB) is associated with increased cardiovascular mortality and heart failure. On the contrary, the clinical relevance of incomplete left bundle branch block (iLBBB) is less known. This study investigated the profile and outcome of iLBBB patients and assessed the risk of progression to cLBBB. Methods: Patients diagnosed with iLBBB between July 2013 and April 2018 were retrospectively included. Subsequently, echo‐ and electrocardiographic examinations at time of iLBBB diagnosis and during follow‐up, as well as progression to non‐strict cLBBB and strict cLBBB, were evaluated. Results: The study enrolled 321 patients (33% female, age 74 ± 11 years). During the follow‐up of 21 (8;34) months, 33% of iLBBB patients evolved to non‐strict cLBBB and 27% to strict cLBBB. iLBBB patients who evolved to non‐strict or strict cLBBB were older, had more frequently reduced left ventricular ejection fraction, and had more often QRS notching/slurring in the lateral leads and inferior leads, compared to patients without progression to cLBBB. In multivariate analysis, only QRS notching/slurring in the lateral leads was independently associated with progression to non‐strict cLBBB (odds ratio 4.64, p < .001) and strict cLBBB (odds ratio 9.6, p < .001). iLBBB patients with QRS notching/slurring had a progression rate to non‐strict cLBBB of 52% and 49% to strict cLBBB. Conclusion: Among patients with iLBBB, up to one third of the patients progress to cLBBB within a period of 2 years. The presence of QRS notching/slurring in the lateral leads during iLBBB was the strongest predictor for progression toward cLBBB.